Assessment and Principles of Environmentally Sustainable Food and Agriculture Systems - Çakmakçı, Ramazan; Salık, Mehmet Ali; Çakmakçı, Songül (Agriculture (Basel), 2023)
Feeding the world depends on protecting our valuable ecosystems and biodiversity. Currently, increasing public awareness of the problems posed by the current industrialized food system has resulted in increased support for the creative market for economically, socially, and ecologically sustainable food production systems and enhanced demands for variations in agricultural policies and regulations. In food production, the restoration and protection of ecosystems and sustainable food systems must be given priority, which requires a forward-looking rational management strategy and fundamental changes in patterns and practices of economic development, product, and production. Food systems should be redesigned to have a neutral and positive environmental impact, as well as ensure healthy nutrition and food safety, and low environmental impact strategies should become a priority. This review paper aims to discuss, build, guide and evaluate sustainable food systems, principles, and transition strategies such as agroecological, organic, biodynamic, regenerative, urban, and precision agriculture, which are imperative visions for the management of agriculture and food production. To this end, we analyzed the evolution of the established strategies to develop sustainable agriculture and food systems, and we created assessment of key sustainability issues related to food, environment, climate, and rural development priorities and resource use practices.